Development of the concept of living thing through age: an exploratory study addressing pupils from two different years of schooling - Almeida, António (2020)
This study sought to check the understanding of living thing in pupils from two different years of schooling. To this end, a questionnaire was applied to 20 pupils who were in the 3rd year of schooling (mean age 8.5) and 15 students in the 5th (mean age 11). In both groups, the topic had been addressed in a formal context through a traditional approach with interactive lectures and use of the textbook. In the questionnaire the pupils had to mark the living things presented in a series of images and to indicate the characteristics of this type of beings. The results showed a better performance of pupils from the 5th, who revealed fewer misconceptions related to the topic. However, some pupils in both groups have revealed more difficulty in the identification of the features common to all living beings. Some implications of the results for teaching practice are discussed at the end of the text.